(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The purpose of the study was to investigate the vulnerability viability of the girl child in selected single -sex secondary schools of Lusaka district of Zambia. The study objective was to establish the profile of a vulnerable girl child in selected single -sex secondary schools. The used adopted the qualitative approach and used a phenomenological research design. The study population included all the single girls schools in Lusaka district. The sample comprised of 38 participants who included 8 vulnerable girls in each school and 4 guidance teachers. Interviews were used to collect data from the guidance teachers while focused group discussions were used to collect data from pupils. Data was analysed thematically by coding the data, selecting what should be presented under themes which emerged from the study. The study found that the vulnerable viabilities included lack of proper dietary habits and good nutrition. Under household responsibilities, girls were overworked at home and performed many chores which made them to underperform in schools. Meanwhile, economic vulnerability included lack school materials like bookracks, desks, and brooms, lack of money for school upkeep, lack of proper school uniforms, shoes, socks, jerseys, necktie, and no lunch money. The other vulnerability was lack of resources and support for education. The parents of the vulnerable girl children cannot afford school extra tuition, school related books and materials. Lastly was the emotional vulnerability which included various emotional abuses which the learners underwent in the community and school indirectly and directly. The study concludes that secondary school girls were vulnerable differently in the secondary schools and these should be looked at with critical analysis for learners to excel in schools. The study recommends that teachers and parents should work together to ensure that they support their children for them to perform better in the Zambian education system.